PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP ALOKASI BELANJA MODAL PADA PEMERINTAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Indra Sulistyaningsih; Haryanto Haryanto (Diponegoro Journal of Accounting, 2019)
This study aims to obtain empirical evidence and analyze the influence of Own Source Revenue (PAD), General Allocation Funds (DAU) and Special Allocation Funds (DAK) on Allocation of Capital Expenditures based on Law Number 23 of 2014 concerning Regional Government. The sample are 29 districts and 6 cities in Central Java Province which submitted Local Government Financial Reports (LKPD) during period of 2013 to 2017. The sample was chosen using a census method and obtained observations of 175 samples, after checking there are outlier data as 6 so the total final sample as many as 169 samples. The analytical method in this study is multiple linear regression analysis using IBM SPSS software. The results of this study indicate that Own Source Revenue (PAD), General Allocation Funds (DAU) and Special Allocation Funds (DAK) have a significant positive effect on Allocation of Capital Expenditures.